The Effect Of Wound Care With Olive Oil On Pressure Ulcer Healing In Older Adults: A Systematic Review - Handayani, Eka Sila; Sahar, Junaiti; Rekawati, Etty; Eka Putri, Yossie Susanti (Jurnal Riset Kesehatan, 2025)
Background: Pressure ulcers are a significant concern commonly encountered by the elderly, both in medical institutions and domestic settings. The worldwide incidence of pressure ulcers in the elderly varies from 3.3% to 11.1%. In Indonesia, 95% of the elderly are autonomous, although 5% exhibit varied degrees of reliance, ranging from mild to complete. Preventive interventions include wound care, adequate nutrition, regular position changes, and the use of moisturizers such as olive oil. Aim : To determine the effect of using olive oil in the care of pressure ulcers in the elderly. MethodThe researcher used a systematic literature review method with five databases: Clinical Key, PubMed, Garuda, SAGE, and ProQuest, focusing on publications from 2015 to 2024. The included studies were Randomized Controlled Trials and Case-Control Studies that involved elderly > 60 years old participants as samplesResults: Based on the literature review, three RCT and quasi-experimental articles indicated that olive oil is effective in reducing the severity of pressure ulcers and the risk of worsening. Conclusion: Based on the research articles reviewed and analyzed, olive oil has been proven effective in preventing and accelerating the healing of stage 1 and 2 pressure ulcers, with a large effect size (Cohen’s d ≈ 0.97–1.5). Olive oil can be considered as a treatment option for pressure ulcers in the elderly due to its accessibility and affordability.